Thoreau at two hundred : essays and reassessments - Case, Kristen; Van Anglen, Kevin P.
"This volume examines Thoreau's life, writings and thought on the 200th anniversary of his birth. Written by distinguished scholars of Thoreau's life and works, it provides a comprehensive examination of Thoreau's continued relevance today. Subjects covered include Thoreau and the environment, his economic models in Walden, his relation to Native Americans and African Americans, his involvement with the Free Soil movement and abolition, his later reputation, Concord and its history, the Civil War and literary nationalism, his transnational understanding of time and space, his relation to Samuel Taylor Coleridge, literary expressions of our ongoing ecological crisis, and Thoreau as a philosopher and as an exemplar of new dimensions in American religion and spirituality. This book argues that Thoreau was drawn toward empirical, materialist and local, yet also holistic, cosmic and global understandings of nature and experience. It will be of interest to all scholars of Thoreau, and also to American literary studies more widely"--